Abuse by association: migration from terror-prone countries and human rights abuses. Issue 2 (4th March 2021) - Avdan, Nazli; Bsisu, Naji; Murdie, Amanda
ABSTRACT: A burgeoning body of work examines the connection between migration and security. Studies link migration to an increased volume of terrorism in destination states. More recent work examines the humanitarian consequences for political migrants and shows that refugees confront repression by state agents in recipient states. We argue that these consequences can generalize to society writ large and may point to a broader erosion of human rights. We build on and expand this line of work by examining the effects of migration on the abuse of physical integrity rights in destination states. Using a cross-national longitudinal sample from 1980 to 2010, we show that while overall migration has no pernicious effects, migration flows from terror-prone states are associated with reduced physical integrity rights provision in destination states. Contrary to intuition, we find that migration from culturally dissimilar origin states has no negative consequences. These results refine our understanding of the migration-security nexus by showing that fears over terrorism drive the deleterious consequences of migration. Our paper also contributes to the human rights literature by demonstrating that the link between migrants and terrorism affects the rights not just of foreigners but also those of destination citizens.